(untitled) (SigMe, 2025)
In the Community Obstetrics courses of the Midwifery degree Programme (School of Medicine, Udelar), a sustained trajectory has been established within the community as well as the University’s Extension activities. Within this framework, various initiatives have been developed in Municipality F of Montevideo, Uruguay, giving continuity from 2022 to five projects focused on parenting, childcare, puerperium and breastfeeding at the Mainumbi early childhood care center. Globally, breastfeeding is recognized for its health, economic and cultural benefits. However, the decrease in breastfeeding rates represent a public health concern, prompting international strategies to promote exclusive breastfeeding during the first six months of life. This extension space accompanies families in the postpartum period, offering guidance on human breastfeeding at each developmental stage, safe sleep practices, respectful weaning and ergonomic babywearing. In addition, it provides tools to recognize physiological changes, validate emotions and navigate this stage with greater well-being. The exchange of experiences fosters a supportive space where families can feel understood, reducing the feeling of loneliness and and isolation, and addressing emotions such as guilt or distress, thus strengthening motherhood and fatherhood with more resources for care and well-being.